Abrasive wear of two glass ionomer cements after simulated toothbrushing - Freitas, Márcia Furtado Antunes de; Imai, Leandro Jum; Freitas, César Antunes de; Bianchi, Eduardo Carlos [UNESP]; Almeida, Carina Thaís de; Martins Filho, Ismar Eduardo (My University, 2011)
Introduction and objective: Glass ionomer cement, which was first introduced in Dentistry in 1972, presents good qualities such as aesthetics, fluoride release and adhesion to dental tissues. Because of its preventive characteristics regarding to dental caries, glass ionomer cement has been used for Atraumatic Restorative Treatment (ART), as reported by Frencken and Holmgren [6], meeting the principles announced by the World Health Organization (WHO) for application to large population groups without regular access to dental care. Material and methods: In this present study, the abrasive wear strength of two glass-ionomer cements (Vidrion R® and ChemFlex®) was evaluated through toothbrushing machine. Classic® toothbrushes with soft bristles and Sorriso® dentifrice were also used for the study. Results: Student-t test showed significant difference between both groups, with tobs value = 9.4411 at p < 0.05. Conclusion: It can be concluded that the wear rate caused by toothbrush/dentifrice was higher for Vidrion R® (52.00 mg) than ChemFlex® (5.57 mg).